Combination of wound healing with 1-methylcyclopropene and wound detection by iodine solution to maintain the quality of sweet potato during long-term storage - Cao, Jixuan; Liu, Pei; Wang, Xuejiao; Wang, Qingguo; Shi, Jingying (International Journal of Agricultural and Biological Engineering, 2021)
Wound healing treatment after harvest is a critical step to protect sweet potatoes from pathogens. The method of phloroglucinol staining is commonly used for detecting callus. However, this method is not easy to identify the degree of callus as the color change is not obvious compared with non-curing roots for some cultivars. A new method based on the principle of starch test by iodine was developed for the detection of wound healing. After healing, the reducing sugar content increased while the starch content decreased to a lower level compared to that of the non-curing roots. Moreover, the antioxidant capacity of the sweet potato after wound healing was higher than that in the control. Wound healing combined with ethylene, 1-methylcyclopropene (1-MCP), chlorpropham or abscisic acid were studied for inhibiting sprout of sweet potato root caused by high temperature during curing. The results showed ethylene and 1-MCP treatment had no negative effect on wound healing. Moreover, 1-MCP treatment was the most effective one on the suppression of sprouting and decay of sweet potato. The results indicate that iodine solution staining is a useful and rapid method to identify the wound healing extent, and 1-MCP treatment can effectively inhibit root sprouting during wound healing and the subsequent long-term storage.Keywords: sweet potato, wound healing, iodine staining, sprouting inhibition, decay rateDOI: 10.25165/j.ijabe.20211403.5735Citation: Cao J X, Liu P, Wang X J, Wang Q G, Shi J Y. Combination of wound healing with 1-methylcyclopropene and wound detection by iodine solution to maintain the quality of sweet potato during long-term storage. Int J Agric & Biol Eng, 2021; 14(3): 241–246.